Exergoeconomic and exergoenvironmental analysis of a coal-fired thermal power plant - Düzcan, Abdullah; Kara, Yusuf Ali (Springer Science and Business Media Deutschland GmbH, 2021)
When evaluating a thermal system, exergy analysis is performed in addition to energy analysis to determine the location and quantity of losses in the system. In this study, energy, exergy, exergoeconomic and exergoenvironmental analyses of Orhaneli thermal power plant located in Bursa are carried out. In exergy analysis, physical and chemical exergies are taken into consideration and potential and kinetic exergies are neglected. Exergoeconomic analysis is conducted by using specific exergy costing (SPECO) method and cost values corresponding to each exergy flows are calculated. According to exergoeconomic analysis, unit exergy cost and exergy cost of steam sent to high-pressure turbine are calculated as 17.94 $/GJ and 22,854 $/h, respectively. The highest exergoeconomic factor is measured in pump (P2) and followed by P3. For the life cycle assessment (LCA) analysis, eco-indicator 99 impact assessment method is selected. LCA results are transferred to exergy flows and then exergoenvironmental analysis is performed. Environmental impact per exergy unit and exergetic environmental impact rate of the steam sent to high-pressure turbine are calculated as 14,680 mPts/GJ and 18,700 Pts/h, respectively. The highest exergoenvironmental factor is measured in pump (P2) and followed by P3.
Keywords: Coal-fired; Eco-indicator 99; Exergoeconomic analysis; Exergoenvironmental analysis; Exergy; Life cycle assessment